Granuloma faciale: clinical, morphological and immunohistochemical aspects in a series of 10 patients - Cristiano Claudino Oliveira; Pedro Eugênio de Carvalho Ianhez; Silvio Alencar Marques; Mariângela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2016)
Abstract Granuloma faciale is a chronic, benign, cutaneous vasculitis with well-established clinical and morphological patterns, but with an unknown etiology. This study describes clinical and pathologic aspects of patients diagnosed with granuloma faciale. The authors analyzed demographic, clinical, morphological and immunohistochemical data from patients with a final diagnosis of granuloma faciale, confirmed between 1998 and 2012. There was a proportional and mixed inflammatory infiltrate, Grenz zones were present in almost all the samples. Immunophenotyping confirmed a higher intensity of T lymphocytes than B lymphocytes in thirteen samples, with a predominance of T CD8 lymphocytes in 64% of cases, in contrast to the literature, which indicates that the major component is T CD4 lymphocytes. All cases were positive for IgG4 but the majority (12/14) had less than 25% of stained cells. The pathogenesis of granuloma faciale remains poorly understood, making studies of morphological and immunohistochemical characterization important to better understand it.